Pengaruh Experiental Marketing dan Citra Perusahaan Terhadap Kepuasan Nasabah Pembiayaan Multiguna Sepeda Motor di Bank Sumut KCP Syariah Rantauprapat - Ayu Rizkia Hutagaol; Dewi Manda Anggraini (Universitas 17 Agustus 1945 Semarang, 2024)
Experiential marketing's importance and This study is primarily driven by a desire to understand how Bank Sumut KCP Syariah's corporate image impacts customer satisfaction in Rantauprapat, North Sumatra. The research strategy used in this study is a quantitative correlational approach. The term